2006
DOI: 10.1530/eje.1.02260
|View full text |Cite
|
Sign up to set email alerts
|

Foetal testosterone and the child systemizing quotient

Abstract: This study examines foetal testosterone (fT) levels (measured in amniotic fluid) as a candidate biological factor, influencing sex differences in systemizing. Systemizing is a cognitive process, defined as the drive to analyze or construct systems. A recent model of psychological sex differences suggests that this is a major dimension in which the sexes differ, with males being more drawn to systemize than females. Participants included 204 children (93 female), age 6-9 years, taking part in a long-term study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 41 publications
6
77
2
2
Order By: Relevance
“…However, the current findings were consistent with measurements indicating a link between higher FT levels and increased attention to detail as well as increased systemizing ability in children (Auyeung et al, 2006(Auyeung et al, , 2009b. These findings also support results by Resnick et al (1986), who found that girls with CAH showed enhanced performance on the Hidden Figures test.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the current findings were consistent with measurements indicating a link between higher FT levels and increased attention to detail as well as increased systemizing ability in children (Auyeung et al, 2006(Auyeung et al, , 2009b. These findings also support results by Resnick et al (1986), who found that girls with CAH showed enhanced performance on the Hidden Figures test.…”
Section: Discussionsupporting
confidence: 91%
“…A significant relationship between FT and the''attention to detail''subscale of the Autism Spectrum Quotient-Children's Version in 235 children between 6 and 10 years of age has been observed (Auyeung et al, 2009b). Exposure to FT has also been linked to more masculinized play behavior (Auyeung et al, 2009a) and systemizing (the drive to analyze, explore, and construct a system, measured using the children's version of the Systemizing Quotient) in both boys and girls (Auyeung et al, 2006). Intelligence measures were obtained and these results are reported elsewhere (Auyeung et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…We would expect directly measured digit ratio to be higher than those measured using a photocopy , though not to this extent. Thus, despite the expected sex difference (Manning et al 1998), the expected direction of the relationship with mental rotation (Peters et al 2007) and a comparable magnitude of correlation to other research with mental rotation (Sanders et al 2005) and systemising (Voracek and Dressler 2006) we should interpret the digit ratio data with caution, especially given the larger than expected standard deviation (see Brosnan 2006), and foetal testosterone assayed from amniotic fluid taken during the second semester has been found to correlate with parental ratings of a child's systemizing capabilities in prepubescent children aged 6-9 (Auyeung et al 2006).…”
Section: Discussionmentioning
confidence: 60%
“…Brief version of the SQ -preprint Finally, we extended our findings to a group of transgender participants and found that the scale has similar psychometric properties in this group. Foetal testosterone levels have been implicated in the development of both systemizing and transgenderism (Auyeung et al, 2006;Veale, Clarke, & Lomax, 2010a). This study showed that the measure of systemizing is similar in this group and the difference between males and females remains across people who have atypically gender-typed brains, conceivably due to foetal testosterone levels, whether or not this gender-typing is consistent with one's biological sex.…”
Section: Discussionmentioning
confidence: 58%